Development from the perspective of culture - Martinell Sempere, Alfons (Revista Española de Desarrollo y Cooperación, 2023)
This article reflects on the history and processes for greater inclusion of culture in development cooperation policies. Analyzes the current situation after 2030 agenda didn’t include a specific cultural objective. From the analysis of different studies, working lines for the incorporation of cultural dimensions to development are presented.
Keywords: Culture; SDG Agenda; Development; Cultural diversity; Cooperation